Molecular profiles of hepatotoxicity and nephrotoxicity markers in dysmenorrheic (on treatment or not) students - Sylvie, Ongbayokolak N; Geraldo, Djeudong; Joseph, Bilim B; Bruno, Telefo Phelix (Clinical Journal of Obstetrics and Gynecology, 2020)
Background: Dysmenorrhea is menstrual disorder that affects about 40% - 90% of women worldwide, it is associated with oxidative stress. The current treatment of this condition is administration of non-steroidal anti-inflammatory drugs, which when frequently used, may affect organs. Objective: Assess the hepatotoxicity and nephrotoxicity side effects related to dysmenorrhea and its treatment Materials and methods: A survey (questionnaire) was designed and implemented on 689 female students of the University of Dschang. After this, and following the inclusion criteria, 191 blood samples were collected for assay of hepatotoxicity markers (transaminases, albumin), nephrotoxicity indicators (creatinine, urea, total protein) and the inflammation associated indicators. The measurements were performed on fully automated Olympus AU 400 Analyzer, using standard reagent kits. Results: Subjects with untreated dymenorrhea lasting more than five years had a significantly high level (p < 0.05) of ALT (39.47 ± 15.74 IU/L) and AST (44.37 ± 13.74 IU/L). Transaminases levels were significantly associate (p < 0.01) and positively correlate (0.251 for ALT and 0. 223 for AST) with the disease duration. Dysmenorrheic individuals on medication for more than 9 years had significantly higher ALT (25.14 ± 7.85 IU/L) and AST (35.26 ± 0.70 IU/L) levels (p < 0.05) compared to those under treatment for less than 5 years (19.37 ± 8.27 UI/L and 27.68 ± 8.56 UI/L). The use of analgesics, regardless of the duration of treatment, had normal creatinine clearance (107.44 ± 30.86 ml/min), compared to those treated with either anti-inflammatory drugs (71.56 ± 26.44 ml/min), or a combination of analgesics and anti-inflammatory drugs (81.34 ± 31.97 ml/min), which was significantly reduced (p < 0.05). Conclusion: Dysmenorrhea duration, type and duration of treatment potentially expose participants to liver and kidney disorders.